The Representation of Armenians and the Armenian Question in Turkey’s 11th Grade Secondary School History Textbook - Melkonyan , Kristine (History and Culture, 2025)
Textbooks of Turkish history is considered one of the most influential methods of denial of the Armenian Genocide as well as the formation of negative mindset towards the Armenian people. In the handbooks of Turkish history Armenians are presented under an extremely negative light. The period of Armenian question from 1878 to 1923 is presented with rough errors and deliberate distortions of historical facts. Furthermore, according the logic of handbooks the existence of our people and the Armenian question are considered to be a threat to Turkish national security.